(untitled) (Web of Teachers: Inderscience Research, 2025)
This article explores the characteristics of dyslexic children in primary education and examines scientifically grounded methods of teaching and support. Dyslexia, being a specific learning difficulty related to language processing, affects reading, writing, and phonological awareness. The article discusses the importance of early diagnosis, individual approach, multisensory techniques, and the use of digital educational technologies. The effective organization of the educational process for dyslexic learners is crucial for their intellectual and social development.